Pullback Attractor for Nonautonomous Ginzburg-Landau Equation with Additive Noise - Yangrong Li; Hongyong Cui (Abstract and Applied Analysis)
Long time behavior of stochastic Ginzburg-Landau equations with nonautonomous deterministic external forces, dispersion coefficients, and nonautonomous perturbations is studied. The domain is taken as a bounded interval I in R. By making use of Sobolev embeddings and Gialiardo-Nirenberg inequality we obtain the existence and upper semicontinuity of the pullback attractor in L2(I) for the equation. The upper semicontinuity shows the stability of attractors under perturbations.